PISA 2021 Creative Thinking Instrument for Students: Physics Teachers’ Perceptions - Susilowati, Nur Endah; Muslim, Muslim; Efendi, Ridwan; Samsudin, Achmad (Universitas Islam Negeri Raden Intan Lampung, 2022)
Creative thinking, as one of the 21st century skills, is an ability that must be mastered by individuals, especially in this ever-changing era. Therefore, the demands of teachers are not only limited to training them in learning, but also knowing the profile of students’ creative thinking abilities is also considered very important. The purpose of this study was to describe teachers’ perceptions and interests about the need for creative thinking instruments with the PISA 2021 framework. A total of 30 physics teachers who teach in various provinces in Indonesia were involved as respondents in this study. Respondents are high school physics teachers with characteristics aged 20-40 years, 19 are female, and 11 are male. Based on the results of the analysis, it is known that more than 90% of respondents stated that it is very important to measure students’ creative thinking skills. As many as 83% of respondents stated that they were interested in the PISA 2021 creative thinking ability framework and wanted to try to do a creative thinking ability test with the PISA framework. Thus, teachers have a positive perception of the PISA 2021 creative thinking framework. For this reason, it is recommended for teachers to develop creative thinking instruments with the 2021 PISA framework to measure students' creative thinking skills in learning.